Potential association between PSCA rs2976395 functional variant and pancreatic cancer risk - Corradi, Chiara; Lencioni, Giulia; Felici, Alessio; Rizzato, Cosmeri; Gentiluomo, Manuel; Ermini, Stefano; Archibugi, Livia; Mickevicius, Antanas; Lucchesi, Maurizio; Malecka-Wojciesko, Ewa; Basso, Daniela; Arcidiacono, Paolo Giorgio; et al. (International journal of cancer, 2024)
Correlated regions of systemic interindividual variation (CoRSIV) represent a small proportion of the human genome showing DNA methylation patterns that are the same in all human tissues, are different among individuals, and are partially regulated by genetic variants in cis. In this study we aimed at investigating single-nucleotide polymorphisms (SNPs) within CoRSIVs and their involvement with pancreatic ductal adenocarcinoma (PDAC) risk. We analyzed 29,099 CoRSIV-SNPs and 133,615 CoRSIV-mQTLs in 14,394 cases and 247,022 controls of European and Asian descent. We observed that the A allele of the rs2976395 SNP was associated with increased PDAC risk in Europeans (p = 2.81 × 10-5). This SNP lies in the prostate stem cell antigen gene and is in perfect linkage disequilibrium with a variant (rs2294008) that has been reported to be associated with risk of many other cancer types. The A allele is associated with the DNA methylation level of the gene according to the PanCan-meQTL database and with overexpression according to QTLbase. The expression of the gene has been observed to be deregulated in many tumors of the gastrointestinal tract including pancreatic cancer; however, functional studies are needed to elucidate the function relevance of the association.
Keywords: GPI-Linked Proteins; Carcinoma, Pancreatic Ductal; nádory slinivky břišní; studie případů a kontrol; alely; Humans; běloši; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; Antigens, Neoplasm; Neoplasm Proteins; Middle Aged; DNA Methylation; Asian People; Pancreatic Neoplasms; metylace DNA; Linkage Disequilibrium; lokus kvantitativního znaku; mužské pohlaví; Alleles; nádorové proteiny; antigeny nádorové; duktální karcinom slinivky břišní; GPI-vázané proteiny; vazebná nerovnováha; ženské pohlaví; White People; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; Case-Control Studies; Quantitative Trait Loci; Asijci; Male; Female